5g+4(-5+3g)=-1-g

Simple and best practice solution for 5g+4(-5+3g)=-1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+4(-5+3g)=-1-g equation:


5g+4(-5+3g)=-1-g

We simplify the equation to the form, which is simple to understand
5g+4(-5+3g)=-1-g

Reorder the terms in parentheses
5g+(-20+12g)=-1-g

Remove unnecessary parentheses
+5g-20+12g=-1-g

We move all terms containing g to the left and all other terms to the right.
+5g+12g+1g=-1+20

We simplify left and right side of the equation.
+18g=+19

We divide both sides of the equation by 18 to get g.
g=1.05555555556

See similar equations:

| 2.65=1.8b+3-2.5b | | 2x+5=10x-5 | | .6*x=10 | | 2k+5/3+2/2/3=1/3 | | 2x+4(x-5)=11 | | -0.9b-1.64b=2.794 | | -2.3+0.7x=1+0.6x-1.8x-6.53 | | 5x+5=2x-3 | | -1v+1=-2v+4 | | 15x-4y=6 | | -2.3+0.7x=1+0.6-1.8x-6.53 | | (7+6)2= | | 4x-4+1=21 | | -2.9x-1.5=5.1848+0.3x | | 4(x-4)=40-4x | | y+7=56 | | 36m^5n^2+24m^2n^3-18m^6n= | | 35m^5n^2+24m^2n^3-18m^6n= | | 5x+7=14-13x | | 2y+1=y-1 | | 0.768-b-0.4b=b+1.728 | | x^3-x^2-54x+144=0 | | .02x^2+0.1x-2=0 | | 5x+5-3x=14+3 | | 1.8r+9=-57r-6 | | 16x-9y=-5 | | 5x-24=x+36 | | 2x-5+3x=-4+4x+2 | | .02x^2+.5x-4=0 | | 16t^2+48t+64=0 | | 5x-8=76-7x | | 0.81-0.1v=2.6v-2.4v |

Equations solver categories